The Effect of Time Management Discipline on The Academic Stress Level of PAI Students in Completing Assignments - Nagiya; Egidia Safitri; Wahyu Saputra (Fakultas Agama Islam Universitas Billfath, 2025)
This study examines whether time management discipline affects the level of academic stress among PAI students at IAIN Kerinci. Employing a quantitative method with a descriptive correlational approach, the research involves 55 students selected through simple random sampling. Data were collected using a closed-ended questionnaire comprising a time management scale and an academic stress scale, then analyzed using simple linear regression. The results indicate a significance value greater than 0.05, suggesting no significant influence of time management discipline on academic stress levels. These findings contribute to the literature by demonstrating that time management is not a primary factor in determining students' stress levels, differing from some previous studies that identified a positive relationship between the two. Practically, the results provide insights for educators and policymakers to consider other factors that may have a more substantial impact on academic stress. This study opens avenues for further research with broader approaches, different methodologies, or additional variables to gain a deeper understanding of this phenomenon.